An endogenous lentivirus in the germline of a rodent - Roziah Kambol; Anna Gatseva; Robert J. Gifford (Retrovirology, 2022)
Abstract Lentiviruses (genus Lentivirus) are complex retroviruses that infect a broad range of mammals, including humans. Unlike many other retrovirus genera, lentiviruses have only rarely been incorporated into the mammalian germline. However, a small number of endogenous retrovirus (ERV) lineages have been identified, and these rare genomic “fossils” can provide crucial insights into the long-term history of lentivirus evolution. Here, we describe a previously unreported endogenous lentivirus lineage in the genome of the South African springhare (Pedetes capensis), demonstrating that the host range of lentiviruses has historically extended to rodents (order Rodentia). Furthermore, through comparative and phylogenetic analysis of lentivirus and ERV genomes, considering the biogeographic and ecological characteristics of host species, we reveal broader insights into the long-term evolutionary history of the genus.